Davies, John i Kent, Alexander J. (2017). The red atlas: How the Soviet Union secretly mapped the world - Paül i Agustí, Daniel (Documents d’Anàlisi Geogràfica, 2019)
Davies, John i Kent, Alexander J. (2017) The red atlas: How the Soviet Union secretly mapped the world Chicago: The University of Chicago Press, 234 p. ISBN 978-0-226-38957-8